Penguatan Kesadaran Masyarakat dalam Konservasi Mangrove Melalui Kegiatan Sosialisasi di Kampung Urumb, Kabupaten Merauke - Adrianus Adrianus; Reny Sianturi; Sajriawati Sajriawati; Yosehi Mekiuw; Suwarjono Suwarjono (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
Mangrove ecosystems play an important role in maintaining the balance of coastal environments and supporting the socio-economic sustainability of coastal communities. However, community understanding of the functions and benefits of mangroves still needs to be improved so that coastal resources can be managed sustainably. This community service activity aims to increase community knowledge and awareness of the importance of mangrove conservation through outreach activities for community groups in Urumb Village, Merauke Regency. The activity was conducted on November 20, 2025, through collaboration between PT Internusa Jaya Sejahtera, Musamus University, and the Urumb Village Government. The methods used included the delivery of educational materials, participatory discussions, and the identification of potential mangrove utilization for local communities. The results of the activity showed that participants demonstrated high enthusiasm and an increased understanding of the ecological functions of mangroves as coastal protectors, habitats for aquatic organisms, and carbon sinks. In addition, the community began to understand the economic potential of mangroves, such as traditional fisheries, crab cultivation, and ecosystem-based tourism development. This activity represents an initial step in strengthening community capacity as managers of coastal resources and supporting sustainable mangrove conservation programs in Urumb Village.